Diversity in knowledge search paths and breakthrough technological innovation: Evidence from new energy vehicle firms. - Xiao Yin; Le Song; Ying Pan (PLoS ONE)
Breakthrough technological innovations have heralded a transformative era within the automotive industry. Knowledge search diversity, as the key to acquiring the raw materials for knowledge recombination, enables firms to overcome resource constraints and accelerate the realization of breakthrough technological innovations. This paper integrates the theories of organizational search and knowledge recombination theory and draws upon the relationship between knowledge and industry to distinguish between basic knowledge search diversity and applied knowledge search diversity. It further investigates the distinct relationships between these two forms of knowledge search diversity and their respective contributions to breakthrough technological innovations. We develop research hypotheses and employ a negative binomial fixed-effects regression model to empirically test data from 280 Chinese new energy vehicle (NEV) manufacturers. The results demonstrate that: (1) knowledge search diversity exhibits an inverted U-shaped relationship with breakthrough technological innovation; (2) the inverted U-shaped relationship is steeper for basic knowledge search diversity compared to applied knowledge search diversity; (3) organizational proximity positively moderates the inverted U-shaped relationship between knowledge search diversity and breakthrough technological innovation. The findings provide practical insights into optimizing knowledge search strategies for technological convergence and accelerating the internalization of external resources to foster innovative transformation and upgrading.